Quantitative new findings about formation and origin of pillow lavas in the Yuksekova Arc Complex, Elazig (Eastern Turkey) - Ural, Melek; Aktas, Metehan Alparslan (Gazi Univ, Fac Engineering Architecture, 2023)
The pillow lavas of the Late Cretaceous Yuksekova Complex are examined comparatively in terms of their physical and morphological character in Asker, Mastar, Celemelik and Maden mountains around Elazig. In the study area, pillow lavas with normal diameter (.1m) and mega pillow lavas (> 1m) were found in almost all regions except Mastar Mountains that often have smaller pillows with few oversized ones. The highest flattening rates (Length/Width) of the pillow lavas are in Celemelik Mountains (5.2) and Asker Mountains (5). The lavas are in the low and medium porous rock class according to their pore volume. The highest specific gravity of the pillow lavas is in the range of 2.8 gr / cm3 to 3.1 gr / cm3, and they are in the class of `low-medium density rocks'. It is determined that Celemelik, Asker and Maden Mountains are represented by the most flattened and coarse-sized pillow lavas. This indicates that the pillow lavas in these areas are expected to emerge as lava flows with low viscosity formed in submarine environment having steep topography. All quantitative data, such as pillow morphology, vesicle size and distribution in the samples, point to a relatively steep topography and relatively high depth for submarine eruptions within the Southern Neotethys.
Yüksekova yay karmaşığında yastık lavların oluşumu ve kökenine dair yeni kantitatif bulgular, Elazığ (Doğu Türkiye)
Keywords: Pillow lavas; porosity; specific gravity; viscosity; submarine eruption